Production of Somatic Cell Nuclear Transfer derived cloned calves in the United Arab Emirates. - Shamim Hossein, Mohammad; Mina Kang; Per Olof Olsson; Huijeong Kim; Yura Bae; Han Seock Kim; Ji Young Noh; Kyung Ik Hwang; Son, Young-Bum; Jeon, Yeon Ik; Romeo Abad Angeles; Woo Suk Hwang (Emirates Journal of Food and Agriculture, 2023)
Despite the tremendous advancement in somatic cell nuclear transfer (SCNT) in camels, the generation of cloned calf using SCNT in cows is yet to be reported in the United Arab Emirates (UAE). The present study intended to produce cloned calves in the local environment of the UAE. We surgically collected ear tissue from two high-performance Holstein cows (average production of 71 liter/ day) and established the fibroblast cell line to perform SCNT. Fifty- seven (18.48%) blastocysts were derived from 330 fused oocytes for cell donor A, and 51 (19.14%) blastocysts were generated from 289 fused oocytes for cell donor B. We used 102 recipients for embryo transfer; among those, 53 and 49 recipients received embryos reconstructed with cell donor A and B, respectively. A single blastocyst in transfer media was transferred deep into the horn of the uterus of natural cycling recipient cows by trans cervical method on Day 7; where estrus was considered as Day 0. Non-return to estrus (up to 42 days), early pregnancy, and the live birth rate did not differ significantly for the two donor cells. Four (26.67%) and 1 (7.69%) live calves were produced for cell donor A and B, respectively. Microsatellite analysis of 18 bovine-specific loci confirmed the perfect match of cell donors and cloned calves. This is the first reported case of cloned calves using SCNT in the UAE. Our results could benefit the UAE dairy industry by supporting the locally produced high- performance replacement heifers. Keywords: Bovine; Cloning; In vitro maturation; Oocytes; UAE